2008
DOI: 10.1111/j.1468-1331.2008.02384.x
|View full text |Cite|
|
Sign up to set email alerts
|

Addenbrooke’s Cognitive Examination validation in Parkinson’s disease

Abstract: Addenbrooke's Cognitive Examination appears to be a valid tool for dementia evaluation in PD, with a cut-off point which should probably be set at 83 points, displaying good correlation with both the scale specifically designed for cognitive deficits in PD namely SCOPA-COG, as well as with less specific tests such as MMSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
3
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 38 publications
1
61
3
5
Order By: Relevance
“…Total scores range from 0-100, a higher score indicates better functioning. The ACE-R has demonstrated reliability in a PD population (Reyes et al, 2009). …”
Section: Cognition 10mentioning
confidence: 99%
“…Total scores range from 0-100, a higher score indicates better functioning. The ACE-R has demonstrated reliability in a PD population (Reyes et al, 2009). …”
Section: Cognition 10mentioning
confidence: 99%
“…The ACE-R, designed to be a more thorough cognitive screening tool than the MMSE, includes six subscores evaluating orientation, attention, memory, verbal fluency, language and visuospatial functioning. The ACE-R has high sensitivity and specificity for the diagnosis of dementia in PD using a cutoff score of 83 [Reyes et al 2009], and more recent work has shown it to be a highly useful screen for the diagnosis of MCI in PD using a cutoff score of 89 [McColgan et al 2012]. Moreover, performance on aspects of the ACE-R, particularly the verbal fluency subscore, has been shown to inform the differential diagnosis of Parkinsonian syndromes including PD, PSP and corticobasal degeneration (CBD) [Rittman et al 2013].…”
Section: Implications For Patient Care: Assessment and Counselingmentioning
confidence: 99%
“…The Montreal Cognitive Assessment (MoCA) and the Addenbrooke's Cognitive Examination-Revised (ACE-R) are other brief global cognitive instruments that have been used to evaluate cognition in general population and in patients with PD 3,4 . Many studies reported that these scales can be useful and may be better than the MMSE to detect cognitive impairment in patients with PD 2,5,6,7,8,9,10,11,12,13,14,15 . In Brazil, the MoCA and ACE-R have been translated and adapted for clinical use, but their diagnostic validity in Brazilian clinical settings still remains uncertain 16,17,18,19 .…”
mentioning
confidence: 99%